UML-based Development Process for IEC 61499 with Automatic Test-case Generation - Hussain, T.; Frey, G. (2006 IEEE Conference on Emerging Technologies and Factory Automation, 2006)
Development of distributed control applications within a standard framework was actually the strongest motivation behind the introduction of IEC 61499. Yet, scarcity of its application is due to the fact that the development is more complex as compared to the existing languages and standards. This paper addresses an UML-based development process for IEC 61499 which attempts to consider the aspects related to the utilization of the unique features that this standard brought into the field of industrial control applications. Reliability is an important consideration in this particular realm of software development and apart from formal verification tests are often performed to verify the software components. An automatic test-case generation methodology is introduced to complement the proposed development process.